A Biocultural Dialogue between Thoreau and Taoist Thought: Rethinking Environmental Ethics, Nature, Spirituality and Place - Michael Thompson; Li Xu (Religions, 2023)
A fundamental question of the 21st century centers around the role and place of humans in their environment. Given the great acceleration of consumptive practices engaged in the 20th century, humans stand on the brink of a 6th extinction event. In order to determine our place and role in our global environment, we need to reflect on where we are and what the future will be—we need to focus on the habits of our “co-inhabitation” of the planet. Given the positive and negative impacts of international and global activities, intercultural dialogues are necessary for the care of the ecology of the planet, and one of the most prescient dialogues is between Eastern and Western world views. While much comparative research has been conducted regarding the connection between American Transcendentalism and Chinese ancient philosophy, relatively little philosophical work has been conducted to demonstrate the connectivity between Henry David Thoreau and Taoism. Yet there are, in fact, profound similarities between the American naturalist and Chinese philosophy, in particular Taoism. This paper aimed to discover and manifest the connection and similarities between the philosophy of Thoreau and the ancient worldview of Taoism. Through this comparative study and intercultural dialogue, we seek to trace historical precedents and intercultural dialogue between American Transcendentalism and ancient Chinese philosophy in order to explore the groundwork for a new vision of environmental awareness in order to promote a better future with a community of co-inhabitants and emphasis on the well-being of all.